(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The parabolic trigonometry in the Galilean plane is introduced in analogy to the simple and hyperbolic trigonometries in the Euclidean and Minkowski planes. In this paper we will introduce parabolic functions and their properties in the Galilean plane.